Pengelolaan Sumberdaya Air Terpadu Melalui Pengembangan Kebijakan Pembangunan Berkelanjutan di Cekungan Bandung - Krishna Nur Pribadi; Putu Pribadi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
In the last decade, water is recognized as having economic value. However, the need to conserve water and allocate ¡t to more valuable uses has not always been evident. Meanwhile, the availability of water resources is being threatened by explosive growth of urban activities, uncontrolled industrialization, and expanding population lacking proper sanitation. Perception of drinking water as a social service probably springs from the necessity of water for life. Is has been taken for granted that all people should be guaranteed this vital water as part of their human rights. However, there is a much weaker understanding of what responsibilities and reciprocal obligations should be associated with the established rights. Responsibilities are seldom specified. Obligations of those who receive drinking water are even less clear. Mismanagement of water resources ¡s putting human health and sustainable development at risk A concern for management of water resources under increasing scarcity and societal stress, including financial constraints and with due consideration to the functioning ecosystems, ¡s a key challenge. To be more focused, this paper will only discuss about water condition and policies which affected the management of water in Bandung Basin. The existing supply and demand condition in Bandung Basin will be provided to give insight of what action should government (and other actors involved) take to overcome the water problems in Bandung Basin.